The Effect of Audiovisual Health Education on Nurse Coping Strategies in the Covid-19 Isolation Room - Dendy Kharisna; Fatmawati Zagoto; Fitri Dyna; Iyang Maisi Fitriani (GLOBAL HEALTH SCIENCE GROUP, 2021)
The covid-19 pandemic has had an impact on the psychological well-being of mental health workers such as nurses. Anxiety, panic, and fear appear along with the covid-19 incident. The increasing workload of nurses and the pandemic crisis conditions have put nurses in a stressful situation. There needs to be a good nurse coping strategy in dealing with the stress faced, so that it has a positive impact on the quality of services provided. One way to improve coping strategies is to provide education that can increase nurses' knowledge and coping strategies, especially using audiovisual method. The aim of the study was to determine the effect of audiovisual education on nurses’s coping strategies of in the Covid-19 isolation room. This research is a quantitative research with a quasi-experimental design. The research sample was 33 respondents of the nurse in the covid-19 isolation room at Santa Maria Hospital Pekanbaru. The strategies coping’s data were collected using the Ways of Coping Questionnaire. Data were analyzed using univariate and bivariate analysis. The results showed that most of the respondents were female (93.9%), permanent employees (93.9%), and worked longer than 1 year in the Covid-19 isolation room (87.9%) and most of the respondents (75.8%) ) early adulthood and diploma degree of nursing. The mean value of coping strategy before education was 151,33 and after education was 160,18 with p value 0,006 (<0,05). This means that there is an effect of audiovisual health education on nurses’s coping strategies in the covid-19 isolation room. Thus, it can be said that audiovisual media education is useful in improving nurses’s coping strategies who working in the covid-19 isolation room.